2005
DOI: 10.1111/j.1471-0528.2005.00712.x
|View full text |Cite
|
Sign up to set email alerts
|

SHORT COMMUNICATION: Mental health screening in women with genital tract fistulae

Abstract: There is little information regarding the mental health status of women with genital tract fistulae in developing countries. The aim of this prospective observational study was to screen women at Dhaka Medical College Hospital, Bangladesh (December 2003 to June 2004), and Addis Ababa Fistula Hospital, Ethiopia (June to July 2004), with genital tract fistula for mental health dysfunction. Women presenting to the above institutions were screened using the General Health Questionnaire (GHQ‐28) prior to fistula su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 8 publications
2
60
1
1
Order By: Relevance
“…A higher rate of thinking of suicide (38%) was recently reported among patients with genital fistula in Ethiopia. 5 These observations are in line with recent findings among non-fistula women at Maroua Regional Hospital in Far North Region. 6 Among 96 women interviewed about the attitude towards obstetric fistula, 33% of them said they would hide themselves and 10% said they would consider committing suicide.…”
Section: Discussionsupporting
confidence: 89%
“…A higher rate of thinking of suicide (38%) was recently reported among patients with genital fistula in Ethiopia. 5 These observations are in line with recent findings among non-fistula women at Maroua Regional Hospital in Far North Region. 6 Among 96 women interviewed about the attitude towards obstetric fistula, 33% of them said they would hide themselves and 10% said they would consider committing suicide.…”
Section: Discussionsupporting
confidence: 89%
“…In a hospitalbased observational study of the mental health of fistula patients in Ethiopia and Bangladesh, women with fistula were found to be more likely than the controls (female hospital workers) to screen positive for probable mental health dysfunction: 97% (66/68) and 32% (9/28), respectively [31].…”
Section: Consequences Of Obstetrics Fistulamentioning
confidence: 99%
“…Among those who have undergone surgical repair, health-related quality of life (QOL) is a key issue; however, most studies conducted to date have focused on QOL before rather than after surgery [4,5,7]. In the studies that have assess postsurgical QOL [6,[10][11][12], surgery has been shown to improve social life, physical activity, and psychological condition.…”
Section: Introductionmentioning
confidence: 99%
“…Affected individuals often encounter stigmatization and discrimination [4,5]. Research shows a high risk of mental health dysfunction among women with obstetric fistula [6,7].…”
Section: Introductionmentioning
confidence: 99%